Evaluasi Sistem Informasi Manajemen Perhotelan Berbasis Web pada PT. Xyz - Suryanto, Suryanto (Bina Nusantara University, 2014)
Information system in a company is expected to support their business processes. Therefore, it requires an evaluation of existing information system and provides recommendations hospitality management information system to meet the gap between existing information systems and user needs. The method of this study is divided into two, namely the method of data collection and analysis methods. Methods of data collection using interviews and observation techniques. Methods of data analysis using gap analysis, followed by a costbenefit analysis and IT Balanced Scorecard. The evaluation results through Fit/Gap Analysis states that the implementation of a management information system is feasible and able to meet all user needs. Cost Benefit Analysis provides an assessment of tangible benefits IT Balanced Scorecard provides an assessment of intangible benefits. The results of the two methods stated that the new information system worth to be implemented.